The best of iggy eaudiobook - Barrows, Annie (Iggy, 2020)
From the New York Times bestselling author of Ivy + Bean comes a hilarious new series featuring a high-energy, lovable troublemaker. Meet 9-year-old Iggy Frangi. He's not a bad kid, he's really not. Okay, so he's done a few (a few is anything up to 100) bad things. And okay, he's not very sorry about most of them. People make a big deal about nothing. What's a little pancake here and there? Is that something to get mad about? Iggy doesn't think so. No one got hurt, so there's no problem. No one got hurt except for that one time, that one time when the Best Idea Ever turned into the Worst Idea of All Time. Iggy is sorry he did it. He is really, really, really sorry. "For what?" you might ask. "What did he do?" Well, you'll have to read the book to find out. Things Iggy will NOT do in this book: Be the most polite kid ever. Play the cello. Think before acting. Learn a lesson. Regret his actions. (Most of them, anyway.)